Achievement of one health multi-sectoral collaboration in containment of Rift Valley Fever outbreak, Sudan, Red Sea State 2019 - Hussein, Hanadi E.; Hassanain, Sara; Okwarah, Patrick; Elbadri, Omer (Published by Oxford University Press on behalf of the European Public Health Association, 2025)
Rift Valley Fever is endemic in Sudan, with a notable outbreak declared in 2019, affecting multiple states. In this study, we examine the Red Sea State, Sudan’s experience in applying the One Health approach, to contain Red Sea RVF outbreak. A retrospective analysis of national and sub-national data and a review of literature were conducted to assess the application of One Health response and to derive lessons learned. The analysis revealed a total of 576 human cases and two deaths, with a case fatality rate of 0.35%, from 25 September 2019 to 25 January 2020. Most cases (99%) were from the Red Sea and River Nile States, and only six sporadic cases were from other five states. The Red Sea State reported 322 human and 74 animal cases, including 74 abortions and 12 animal deaths. Triggers and risk factors include floods, uncontrolled movement of animal, close contact with animals, poor disposal, and unsafe burial practices for animals. One Health approach was utilized all through the defeat of outbreak. A multi-sectoral response plan was implemented, leading to the declaration of the end of the outbreak in 2020 which was reviewed and lessons were derived. One Health approach provided a coordinated action between health, veterinary, and environmental authorities at national and subnational levels. Synergistic efforts have minimized risk of RVF spreading among human and animal. The experience was leveraged to strengthen response approaches for zoonotic diseases. Structural and capacity gaps and financial constraints were identified as implementation challenges.